Nanocellulose reinforced flexible composite nanogenerators with enhanced vibrational energy harvesting and sensing properties - Ram, Farsa; Gudadhe, Aniket; Vijayakanth, Thangavel; Aherrao, Swapnil; Borkar, Vivek; Boomishankar, Ramamoorthy; Shanmuganathan, Kadhiravan (2020)
We report here enhanced vibration and pressure sensing properties of nanocellulose reinforced flexible composite piezoelectric nanogenerators (PENGs). Surface fluorinated nanocellulose crystals (FNC) were incorporated into poly(vinylidene fluoride) (PVDF) and electrospun into composite nanofibers. Incorporation of only 2 wt % FNC in PVDF resulted in a significant enhancement in pressure sensitivity with a very low detectable pressure limit of 10 Pa and a sensitivity of up to 18 mV/kPa. The composite PENGs also demonstrated very high sensitivity for forced continuous vibrations. 2FNC/PVDF composites resulted in an order of magnitude higher voltage response over neat PVDF for a given strain. When PENGs were mounted on a vacuum pump for transduction of mechanical vibrations into electrical energy, 2FNC/PVDF composite devices manifested similar to 3.8 times enhanced voltage output over neat PVDF and faster charging of a capacitor. The enhanced piezoelectric properties of PVDF/FNC nanocomposites could be attributed to the tailored interface between PVDF and nanocellulose and enhanced polarizability.
Keywords: Composite; Nanofiber; piezoelectric; pressure; Sensor; vibration

Flexible energy harvester from an organic ferroelectric ammonium salt - Gupta, Rishabh; Sahoo, Supriya; Deswal, Swati; Kothavade, Premkumar; Dixit, Prashant; Zareba, Jan K.; Shanmuganathan, Kadhiravan; Boomishankar, Ramamoorthy (Chemistry-An Asian Journal, 2021)
Organic ferroelectrics due to their low cost, easy preparation, light weight, high flexibility and phase stability are gaining tremendous attention in the field of portable electronics. In this work, we report the synthesis, structure and ferroelectric behavior of a two-component ammonium salt 2, containing a bulky [Bn(4-BrBn)NMe2](+) (Bn=benzyl and 4-BrBn=4-bromobenzyl) cation and tetrahedral (BF4)(-) anion. The structural analysis revealed the presence of rich non-classical C-H...F and C-H...Br interactions in this molecule that were quantified by Hirshfeld surface analysis. The polarization (P) vs. electric field (E) hysteresis loop measurements on 2 gave a remnant polarization (P-r) of 14.4 mu C cm(-2) at room temperature. Flexible polymer composites with various (5, 10, 15 and 20) weight percentages (wt%) of 2 in thermoplastic polyurethane (TPU) were prepared and tested for mechanical energy harvesting applications. A notable peak-to-peak output voltage of 20 V, maximum current density of 1.1 mu A cm(-2) and power density of 21.1 mu W cm(-2) were recorded for the 15 wt% 2-TPU composite device. Furthermore, the voltage output generated from this device was utilized to rapidly charge a 100 mu F capacitor, with stored energies and measured charges of 156 mu J and 121.6 mu C, respectively.
Keywords: Dielectric; energy harvesting; ferroelectricity; organic composites; piezoelectric

Highly compressible ceramic/polymer aerogel-based piezoelectric nanogenerators with enhanced mechanical energy harvesting property - Ram, Farsa; Suresh, Karthika; Torris, Arun; Kumaraswamy, Guruswamy; Shanmuganathan, Kadhiravan (Ceramics International, 2021)
Ceramic piezoelectric materials have orders of magnitude higher piezoelectric coefficients compared to polymers. However, their brittleness precludes imposition of large strains in mechanical energy harvesting applications. We report here that ice templating affords low bulk modulus lead-free aerogel piezoelectric nanogenerators (PENG) with unprecedented combination of flexibility and high piezoelectric response (voltage and power density). A modified ice templating protocol was used to fabricate piezoelectric nanocomposites of surface modified BaTiO3 (BTO) nanoparticles in crosslinked polyethylene imine. This protocol allowed incorporating a significantly high fraction of BTO particles (up to 83 wt %) in the aerogel, while retaining remarkably high compressibility and elastic recovery up to 80% strain. The output voltage, at an applied compressive force of 20 N (100 kPa), increased with BTO loading and a maximum output voltage of 11.6 V and power density of 7.22 ?W/cm2 (49.79 ?W/cm3) was obtained for PENG aerogels containing 83 wt% BTO, which is orders of magnitude higher than previously reported values for foam-based piezoelectric energy harvesters. The BTO/PEI PENGs also showed cyclic stability over 900 cycles of deformation. PENGs with higher porosity showed better elastic recovery and piezoelectric properties than lower porosity and higher BTO content aerogels. To the best of our knowledge, this is the first report to demonstrate the piezoelectric properties of high ceramic content aerogels having very high compressibility and elastic recovery.
Keywords: Ceramic polymer aerogels; energy harvesting; ice templating; piezoelectric